Penerapan Permainan Tradisional Dalam Pembelajaran Olahraga di SMAN 1 Baradatu - Dwi Handoko; Aditya Gumantan (Journal of Physical Education, 2021)
AbstractThe purpose of research to know student interest in sport learning with traditional game models other than for conserve one of Indonesian cultural wealth that is tradisonal game. The approach using qualitative descriptive method, the subject used student from class XI SMAN 1 Baradatu. Data collection techniques used observation, interviews, and questionnaires. Data analysis from this study used data reduction,presentation, and conclusions. In this study, students were given a questionnaire after the implementation of traditional games in sport learning. The results of this study indicate that students' interest in sport learning using the traditional game model gets a questionnaire answer in the congklak game 76.60%, then the stilt shell game 67%, the top game 60%, and the engklek game 60%, and slingshot games 63.64% and as for the results of students' interest in playing the traditional games that have been developed show that the congklak game gets 77%, then the stilt shell game gets 83%, and the top game gets 80%, then the engklek game gets 73%, and the catapult game gets 92.86% . With the results that have been obtained that students' interest in sport learning by traditional game model is very good and students are interested, as well as the results of students' interest in traditional games that have been developed.So it can be concluded that students are very interested in playing the latest model games.Keywords: Traditional Games, Sport Learning.